Chlorine-functionalized reduced graphene oxide for methylene blue removal1. Issue 65 (16th July 2015) - Wang, Chubei; Zhou, Jianwei; Chu, Liangliang
<x xml:space="preserve">Abstract</x> Hydroxyl group in graphene oxide can be substituted by chlorine in sulfuryl chloride at mild condition.